2004
DOI: 10.1536/jhj.45.109
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Perlecan Gene Intron 6 BamHI Polymorphism and Risk of Mitral Valve Prolapse in Taiwan Chinese

Abstract: SUMMARYAbnormalities of proteoglycan, collagen, and elastic fibers were found in floppy mitral valves. Perlecan is one of the three major classes of heparan sulfate proteoglycans within the cardiovascular system. The role of perlecan genetic variant in mitral valve prolapse (MVP) has not been studied. We therefore performed a case-controlled study investigating the possible relation between the perlecan gene intron 6 BamHI polymorphism and MVP among the Chinese population in Taiwan.We studied 100 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
3
2
Order By: Relevance
“…Transforming growth factor-h1 (TGF-h1) was proposed to be involved in fibrotic process [33]. However, we did not find an association between TGF-b1 polymorphisms and MVP in our population [34]. Histological and ultrastructural analyses of FMV show alterations of collagen, elastic fibers and accumulation of proteoglycans.…”
Section: Discussioncontrasting
confidence: 69%
“…Transforming growth factor-h1 (TGF-h1) was proposed to be involved in fibrotic process [33]. However, we did not find an association between TGF-b1 polymorphisms and MVP in our population [34]. Histological and ultrastructural analyses of FMV show alterations of collagen, elastic fibers and accumulation of proteoglycans.…”
Section: Discussioncontrasting
confidence: 69%
“…TGF-h1 was proposed to be involved in fibrotic process [35]. However, we did not find an association between TGF-b1 polymorphisms and risk of FMV/MVP in our population [36]. The possible contribution of collagenolytic activity (cathepsin B or metalloproteinases) in these valves needs to be evaluated.…”
Section: Discussioncontrasting
confidence: 57%
“…It is interesting that perturbations in autonomic, neuroendocrine, and renin-angiotensinaldosterone system regulation have been reported among symptomatic patients with MVP. 31 A number of studies have subsequently demonstrated genetic association between MVP syndrome and the components of the renin-angiotensinaldosterone system, namely an angiotensin I-converting enzyme insertion/deletion polymorphism in intron 16, 50 the TT genotype of the angiotensinogen Met235Thr polymorphism, 51 and the C allele of the angiotensin II type 1 receptor A1166C polymorphism, 52 although these studies are limited by the relatively small cohort of patients with MVP syndrome. Therefore, although abnormal autonomic function might be responsible for symptoms in some patients with MVP, it remains unclear whether their MVP is directly related or incidental.…”
mentioning
confidence: 99%